Adaptation and Validation of the International Pelvic Pain Society's Quality of Life Questionnaire in Portuguese - Letícia Ferracini Lenharo Hayashi; Paulo Augusto Ayroza Galvão Ribeiro; Júlio Cesar Rosa e Silva; Luiz Gustavo Oliveira Brito; Helizabet Salomão Abdalla Ayroza Ribeiro (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2023)
Abstract Objective In the present study, our aim was to translate, adapt, and validate the Pelvic Health History Form (a quality of life [QoL] questionnaire) of the International Pelvic Pain Society (IPPS) from English to Portuguese. Methods The study was approved by the Ethics and Research Committee (CEP, in the Portuguese acronym) and the IPPS. The "Transcultural Adaptation" method comprised 5 stages: translation, synthesis, backtranslation, expert review, and pretest. Cultural adaptation and validation included cognitive interviews and statistical analysis of unanswered items (> 15%) in 14 clinic patients from CPP and endometriosis clinic at Santa Casa de São Paulo. Results Strong equivalences were established between the USA and Brazil questionnaires in terms of semantics, idioms, experiences, and concepts. Eighteen culturally inappropriate items were identified and adjusted using the revised response rate index. The subjective form underwent rigorous assessments, confirming its accurate measurement of intended targets. Conclusion The methodology showed efficiency and equivalence, confirming its validity. The user-friendly format and inclusion of translated, adapted, and validated instruments in Portuguese make the form valuable for evaluating pelvic health, with potential for future research.